1978
DOI: 10.1159/000241079
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin, Prolactin and Growth Hormone Response to Synthetic Thyrotropin-Releasing Hormone in Newborn Infants

Abstract: The effects of 50 μg synthetic thyrotropin-releasing hormone (TRH) intravenously on thyrotropin (TSH), prolactin (PRL) and growth hormone (GH) levels were studied in 8 normal male newborns during the first hours of life. Mean plasma GH concentrations were similar to baseline values during the period of study; on the contrary, plasma PRL and TSH values increased in all infants after TRH administration. These data demonstrate a normal pituitary reserve of PRL and TSH in the early period of human life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

1980
1980
1986
1986

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
4
1
Order By: Relevance
“…The basal GH levels measured in this study were lower than those reported by other investigators [2,6]. Al though we have no idea about the reason, it might be due to the difference of the kit used for GH titration, because some authors [3,10] reported values near ours even in the study on younger neonates.…”
Section: Discussioncontrasting
confidence: 78%
“…The basal GH levels measured in this study were lower than those reported by other investigators [2,6]. Al though we have no idea about the reason, it might be due to the difference of the kit used for GH titration, because some authors [3,10] reported values near ours even in the study on younger neonates.…”
Section: Discussioncontrasting
confidence: 78%
“…The ele vated neonatal PRL levels arc thought to be due to increased estrogen levels, which stim ulate the turnover of the hypothalamic domapine pool and thereby influence PRL se cretion [11,23,35], The effect of MTC upon the release of PRL has been studied after acute and chronic therapy in adult humans [12,16] and children, and it was demon strated to produce similar alterations to those found in the present study [14], Our data suggest that MTC is a potent stimulus of PRL release already in the early neonatal period and it may be used to assess pituitary PRL reserve in the neonate as efficiently as the TRH test [7], In this study MTC produced no signifi cant alterations in serum levels of TSH, FT4 and Tv Scanlon et al [31 ] explained the lack of TSH release in response to MTC through the inhibitory effects of circulating thyroid hormones, because in hypothyroid patients with very low hormone levels there was a sig nificant TSH release after MTC administra tion. In contrast.…”
Section: Discussionsupporting
confidence: 69%
“…While the PRL responses to exercise, arginine and insulin-induced hypoglycemia gave conflicted results, an enhancement of PRL release after TRH and metoclopramide has been reported in all healthy subjects studied (L'Hermite et al 1977;Delitala et al 1978). It was postulated that the greater GH response might reflect the fact that a demand for oxidizable substrates, rather than the less specific factors of stress, is probably the principal stimulus for GH during exercise.…”
Section: Discussionmentioning
confidence: 97%
“…Synthetic pyroglutamyl-histidyl-prolinamide or thyrotropin-releasing hormone (TRH) stimulates secretion of PRL and TSH, and its administration has become established as a useful test of pituitary function in a number of clinical situations (Tashjian et al 1971;Bowers et al 1971;Jacobs et al 1971;Guyda and Friesen 1973;Noel et al 1974;Bremner et al 1977;L'Hermite et al 1977;Delitala et al 1978;Ayalon et al 1979;Kopelman et al 1979). TRH induced a rapid increase in circulating PRL and maximal release was reached within 15 min, earlier than that of TSH release.…”
Section: Discussionmentioning
confidence: 99%